2017
DOI: 10.1371/journal.pone.0184597
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of different transarterial embolization therapies alone or in combination with local ablative or adjuvant systemic treatments for unresectable hepatocellular carcinoma: A network meta-analysis of randomized controlled trials

Abstract: BackgroundThe optimal transcatheter embolization strategy for patients with unresectable hepatocellular carcinoma (HCC) remains elusive. We conducted a systematic review and network meta-analysis (NMA) of different embolization options for unresectable HCC.MethodsMedical databases were searched for randomized controlled trials evaluating bland transarterial embolization (TAE), conventional TACE, drug-eluting bead chemoembolization (DEB-TACE), or transarterial radioembolization (TARE), either alone or combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 117 publications
1
71
0
4
Order By: Relevance
“…Indeed, with 5‐year overall survival rates of up to 75%, ablation has been validated as an alternative to resection for very small tumours (Barcelona Clinic Liver Cancer classification [BCLC] stage 0) and patients with limited disease non‐resectable because of associated liver disease (BCLC stage A) . In addition, ablation has shown promising results within combination therapies for advanced disease and is commonly used as bridging to OLT (as recommended by the current AASLD and EASL guidelines) . The major advantage of ablation lies in its minimal‐invasive tissue‐sparing yet locally destructive character, with short hospital stays and low morbidity .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, with 5‐year overall survival rates of up to 75%, ablation has been validated as an alternative to resection for very small tumours (Barcelona Clinic Liver Cancer classification [BCLC] stage 0) and patients with limited disease non‐resectable because of associated liver disease (BCLC stage A) . In addition, ablation has shown promising results within combination therapies for advanced disease and is commonly used as bridging to OLT (as recommended by the current AASLD and EASL guidelines) . The major advantage of ablation lies in its minimal‐invasive tissue‐sparing yet locally destructive character, with short hospital stays and low morbidity .…”
Section: Introductionmentioning
confidence: 99%
“…31 Despite the limited number of randomized studies, several meta-analyses have been published in the attempt to assess the value of combined TACE-RFA compared with monotherapies (►Table 2). [32][33][34][35][36][37][38][39] The majority of these meta-analyses confirmed that the combination therapy is able to significantly improve local tumor control and OS compared with either RFA or TACE, in selected populations. In particular, while there seems not to be any advantage in small and large-size tumors, the combined approach should be indicated for lesions 3 to 5 cm in size.…”
Section: Resultsmentioning
confidence: 66%
“…[13,14] Combined chemoembolization, external radiotherapy, or localized liver ablation are better than embolization alone, prolonging the median survival time by up to 20 months. [13,15] Chemoembolization was performed employing Adriamycin.…”
Section: Discussionmentioning
confidence: 99%